2020
DOI: 10.1001/jamanetworkopen.2020.15036
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health Conditions and Health Service Use Among Transgender Patients in Canada

Abstract: Key Points Question How do sociodemographic characteristics, chronic conditions, and health service utilization trajectories differ among transgender individuals compared with the general population? Findings This cross-sectional study identified and linked health administrative data for 2085 transgender individuals in Ontario, Canada, and found that transgender individuals are more likely to live in lower-income neighborhoods, experience chronic health con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 29 publications
1
30
0
1
Order By: Relevance
“…However, there seems to be a fair degree of heterogeneity between these studies. For instance, one study reported psychiatric comorbidities in 45.8% of a group of transgender children and adolescents [36] while another reported 53.2% of patients with gender dysphoria had at least one psychiatric disorder [37•], a third reported 76.3% of transgender individuals had psychiatric comorbidities [38], and a fourth reported 67.6% of a group of adolescents with gender dysphoria had no co-occurring psychiatric disorders [39].…”
Section: Psychiatric Comorbidities In Transgender Individuals and Those With Gender Dysphoriamentioning
confidence: 99%
“…However, there seems to be a fair degree of heterogeneity between these studies. For instance, one study reported psychiatric comorbidities in 45.8% of a group of transgender children and adolescents [36] while another reported 53.2% of patients with gender dysphoria had at least one psychiatric disorder [37•], a third reported 76.3% of transgender individuals had psychiatric comorbidities [38], and a fourth reported 67.6% of a group of adolescents with gender dysphoria had no co-occurring psychiatric disorders [39].…”
Section: Psychiatric Comorbidities In Transgender Individuals and Those With Gender Dysphoriamentioning
confidence: 99%
“…Transgender people have been shown to have worse general and mental health outcomes than their cisgender counterparts. The reasons for this include stigma, discrimination, minority stress, and socioeconomic differences, among others [37][38][39][40]. The current global pandemic has accentuated health disparities among trans youth and other marginalized identities [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Health administrative data can be useful to examine patterns of mental health care access for populations. Recent studies have explored transgender patients' use of mental health care by using health administrative data in the United States and Canada (12)(13)(14)(15)(16). Studies have found that transgender individuals were more likely to have had psychiatric outpatient visits, hospitalizations, and ED visits (12)(13)(14)(15)(16) than were cisgender people.…”
Section: Highlightsmentioning
confidence: 99%
“…Individuals' Ontario health insurance number and date of birth were used to link individuals to administrative databases at ICES. This process has been previously described (16). All transgender individuals were identified from the study population and included in the two transgender samples in this study.…”
Section: Identifying Transgender Individualsmentioning
confidence: 99%
See 1 more Smart Citation